2015
DOI: 10.1007/s00394-015-0984-0
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate inhibits neuroinflammation and amyloidogenesis in IL-1β-stimulated SK-N-SH cells

Abstract: Conclusions:Taken together, our study demonstrates that pomegranate inhibits inflammation, as well as amyloidogenesis in IL-1β-stimulated SK-N-SH cells. We propose that pomegranate is a potential nutritional strategy in slowing the progression of neurodegenerative disorders like Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…One hour after oral consumption of 180 mg of pomegranate juice, containing 25 mg EA and 318 mg Ellagitannin, the blood level of EA is achieved 31.9 mg/L in human (Velagapudi, Baco, Khela, Okorji, & Olajide, ). Shirode et al evaluated the effects of nano‐encapsulation of pomegranate active ingredients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One hour after oral consumption of 180 mg of pomegranate juice, containing 25 mg EA and 318 mg Ellagitannin, the blood level of EA is achieved 31.9 mg/L in human (Velagapudi, Baco, Khela, Okorji, & Olajide, ). Shirode et al evaluated the effects of nano‐encapsulation of pomegranate active ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…Velagapudi et al evaluated the effects of freeze‐dried pomegranate juice (PWE, 50–200 μg/mL) on IL‐1β‐stimulated human neuroblastoma SK‐N‐SH cells. They demonstrated that PWE markedly alleviates the PGE2 production, IκB and IKK phosphorylation, Beta‐secretase 1 (BACE‐1), COX‐2 and Aβ expression following IL‐1β‐induced inflammation in SK‐N‐SH cells (Velagapudi et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a dose of 1.5 mg/kg punicalagin attenuated LPS (250 μg/kg daily 7 times) induced memory impairment and blocked the LPS-induced expression of inflammatory proteins via suppression of NF-κB activation [80]. In addition, freeze-dried pomegranate (25-200 μg/ml) in a dose-dependent manner reduced COX-2-dependent prostaglandin E2 (PGE2) production in SK-N-SH cells stimulated with IL-1β [81]. The neuroprotective action of pomegranate was obscured in an animal study in which dietary supplementation of 4% pomegranate extract to APPsw/Tg2576 mice for 15 months ameliorated the loss of synaptic structure proteins, inhibited neuroinflammatory activity, and enhanced autophagy (degradation and recycling of cellular components).…”
Section: Parasitic Infection 2531 Preclinical Studiesmentioning
confidence: 99%